2019
DOI: 10.1186/s12885-019-5820-0
|View full text |Cite
|
Sign up to set email alerts
|

EGFR exon 20 insertion mutations and response to osimertinib in non-small-cell lung cancer

Abstract: Background Epidermal growth factor receptor exon 20 insertion (EGFRex20ins) mutations represent approximately 4–12% of EGFR mutations and are generally refractory to the 1st and 2nd generation EGFR tyrosine kinase inhibitors (TKIs). Development of effective therapies for patients with EGFRex20ins mutant non-small-cell lung carcinoma (NSCLC) represents a great unmet need. Preclinical models have shown that osimertinib is active in NSCLC harboring EGFRex20ins, while the antitumor activity of osimert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
93
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 35 publications
13
93
1
1
Order By: Relevance
“…The rapid development of NGS technologies allows for genomic profiling detection of multiple samples from different patients with multiplexed panels (21). The alignment of the sequences from tumor tissue samples and matched blood samples were considered to be an effective method for detecting somatic mutations (22)(23)(24). To date, many studies on potential biomarkers for CCA have been reported (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of NGS technologies allows for genomic profiling detection of multiple samples from different patients with multiplexed panels (21). The alignment of the sequences from tumor tissue samples and matched blood samples were considered to be an effective method for detecting somatic mutations (22)(23)(24). To date, many studies on potential biomarkers for CCA have been reported (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Although more and more studies have confirmed the superior efficacy of Osimertinib in NSCLC paitents with EGFR driver mutations [5,12,[20][21][22], the tumor response and survival outcomes after the treatment of Osimertinib are usually different in patients. The mechanisms of resistance to Osimertinib have been the subject of several clinical studies [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Missing data were not included in the study, which is consistent with previous descriptions [21]. The hazard ratio (HR) and corresponding 95% CIs were estimated using Cox proportional hazards models.…”
Section: Discussionmentioning
confidence: 74%